Sociodemographic and work-related factors associated with psychological resilience in South African healthcare workers - Mcizana, Thandokazi (Department of Public Health and Family Medicine, 2025)
Background: Psychological resilience facilitates adaptation in stressful environments and is an important personal characteristic that enables healthcare workers to navigate the challenges encountered in their occupation. To date, there is not much information available on factors associated with psychological resilience in South African healthcare workers. Objectives: To determine the prevalence, sociodemographic and work-related factors associated with psychological resilience in a group of South African medical doctors and ambulance personnel. Materials and Methods: This analytical cross-sectional study used secondary data obtained from two cross-sectional studies conducted in healthcare workers. This study investigated the factors associated with resilience as measured by the Connor-Davidson Resilience Scale-10. Inferential analysis was computed to assess the association between independent variables and resilience. Results: A total of 647 healthcare workers were included in the study, consisting of 259 doctors and 388 ambulance personnel. The healthcare workers had low resilience scores (27.6 ± 6.6) overall, with ambulance personnel having a higher average resilience score (28.0 ±6.9) compared to doctors (27.1 ± 6.0) (p = 0.006). Significantly higher resilience scores were observed for doctors: in males (p < 0.001), higher income earners (p = 0.020), current smokers (p = 0.012); for ambulance personnel: previous users of alcohol (p = 0.002). Significantly lower resilience scores were observed in participants with a mental health condition (doctors: p = 0.037; ambulance personnel: p = 0.010), being on treatment for a mental health condition (ambulance personnel: p = 0.029) and feeling the need to drink alcohol to manage work-related stress (doctors: p = 0.034; ambulance personnel: p= 0.048). Multivariable analysis confirmed that current smoker status (β: 3.52, 95%CI: 0.89 – 6.16, p = 0.009) and higher salary in doctors (β: 5.11, 95%CI: 1.46 – 8.177, p = 0.006), and previous alcohol use in ambulance personnel (β: 3.22, 95%CI: 1.10 - 5.34, p = 0.003) were protective against low resilience. Female sex (β: -1.77, 95%CI: -3.39 - -0.15, p = 0.032) and over-time work in doctors (β: -5.11, 95%CI: -9.42 - -0.80, p = 0.006) increased the likelihood of low resilience. Conclusions: Resilience was relatively low in this group of South African healthcare workers. The strong association between low resilience and individual and workplace factors such as female gender, lower income, high over-time worked, mental health status and substance use provide avenues for early intervention and provision of greater support to healthcare workers in low-and middle-income settings.